Understanding the effects of nutrition‐sensitive agriculture interventions with participatory videos and women's group meetings on maternal and child nutrition in rural Odisha, India: A mixed‐methods process evaluation. Issue 4 (19th July 2022) - Prost, Audrey; Harris‐Fry, Helen; Mohanty, Satyanarayan; Parida, Manoj; Krishnan, Sneha; Fivian, Emily; Rath, Suchitra; Nair, Nirmala; Mishra, Naba K.; Padhan, Shibanath; Pradhan, Ronali; Sahu, Satyapriya; et al.
Abstract: A trial of three nutrition‐sensitive agriculture interventions with participatory videos and women's group meetings in rural Odisha, India, found improvements in maternal and child dietary diversity, limited effects on agricultural production, and no effects on women and children's nutritional status. Our process evaluation explored fidelity, reach, and mechanisms behind interventions' effects. We also examined how context affected implementation, mechanisms, and outcomes. We used data from intervention monitoring systems, review notes, trial surveys, 32 case studies with families ( n = 91 family members), and 20 group discussions with women's group members and intervention workers ( n = 181 and 32, respectively). We found that interventions were implemented with high fidelity. Groups reached around half of the mothers of children under 2 years. Videos and meetings increased women's knowledge, motivation and confidence to suggest or make changes to their diets and agricultural production. Families responded in diverse ways. Many adopted or improved rainfed homestead garden cultivation for consumption, which could explain gains in maternal and child dietary diversity seen in the impact evaluation. Cultivation for income was less common. This was often due to small landholdings, poor access to irrigation and decision‐making dominated by men. Interventions helped change norms about heavy work during pregnancy, but young women with little family support still did considerable work. Women's ability to shape cultivation, income and workload decisions was strongly influenced by support from male relatives. Future nutrition‐sensitive agriculture interventions could include additional flexibility to address families' land, water, labour and time constraints, as well as actively engage with spouses and in‐laws. Abstract : In rural eastern India, participatory videos and women's group meetings on agriculture and maternal and child nutrition increased women's knowledge, motivation and confidence to improve their and their children's diets. Despite the intervention's emphasis on addressing social and structural constraints to cultivation, small landholdings, poor access to water and the need for in‐laws' or husbands' support to make changes to cultivation patterns led many women to respond to interventions by increasing rainfed homestead garden cultivation for consumption rather than cultivating for income. The interventions' ability to influence the adoption of nutrition‐sensitive agriculture practices could be improved by being family‐centric: understanding women's decision‐making power in a family context, using tailored problem‐solving to address households' individual constraints to cultivation, and including women's spouses and in‐laws. Key messages: In rural eastern India, participatory videos and women's group meetings on agriculture and maternal and child nutrition increased women's knowledge, motivation and confidence to improve their and their children's diets. Given strong constraints linked to small landholdings, poor access to water and gender norms which meant that in‐laws' and husbands' assent or support were often required for cultivation decisions, many women responded to interventions by increasing rainfed homestead garden cultivation for consumption rather than cultivating for income. Women's and children's diets may have improved because of discussions about nutrition and an increase in homestead garden cultivation. These dietary changes alone were likely insufficient to improve women's and children's nutritional status. The interventions' ability to influence the adoption of nutrition‐sensitive agriculture practices could be improved by being family‐centric: understanding women's decision‐making power in a family context, using tailored problem‐solving to address households' individual constraints to cultivation, and including women's husbands and in‐laws.